2004
DOI: 10.34194/geusb.v1.4615
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory notes to the Geological map of Greenland, 1:500 000, Humboldt Gletscher, Sheet 6

Abstract: Dawes, P.R. 2004: Explanatory notes to the Geological map of Greenland, 1:500 000, Humboldt Gletscher, Sheet 6. Geological Survey of Denmark and Greenland Map Series 1, 48 pp. + map. These explanatory notes cover the map region bounded by latitudes 78°N and 81°N and longitudes 56°W and 74°W, with geology shown on the land areas between Nares Strait - the seaway between Greenland and Ellesmere Island, Canada - and the Inland Ice. The bedrock geology is composed of Precambrian and Lower Palaeozoic province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…The gneissosity is moderately well developed in the paragneisses, but can be quite weak in the more massive intrusive rocks. The N-S gneissosity on southeast Ellesmere Island is at a high angle to the E-W gneissosity on Devon Island (Frisch, 1984(Frisch, , 1988 and North-West Greenland (Dawes and Garde, 2004;Nutman et al, 2008). In contrast to the study area, ductile shear zones up to 30 m thick have been observed on Devon Island (Frisch, 1988).…”
Section: Geologic Settingcontrasting
confidence: 51%
“…The gneissosity is moderately well developed in the paragneisses, but can be quite weak in the more massive intrusive rocks. The N-S gneissosity on southeast Ellesmere Island is at a high angle to the E-W gneissosity on Devon Island (Frisch, 1984(Frisch, , 1988 and North-West Greenland (Dawes and Garde, 2004;Nutman et al, 2008). In contrast to the study area, ductile shear zones up to 30 m thick have been observed on Devon Island (Frisch, 1988).…”
Section: Geologic Settingcontrasting
confidence: 51%
“…The Wegener Transform Fault, crossing from Judge Daly Promontory to Kap Lupton (Fig. 2) in the study area and extending northwards in Nares Strait (Dawes, 2004; Tessen- ; JDP is Judge Daly Promontory. Ice flow in marine areas (black arrows) and deglacial ice-sheet margins for the early Holocene (9.3, ∼ 8.7 and ∼ 7.6 ka cal BP) are also shown for Nares Strait and were compiled from England (1999), Georgiadis et al (2018) and Jakobsson et al (2018).…”
Section: Physiography and Hydrographymentioning
confidence: 94%
“…Also, the inaccessible Lauge Koch Kyst has only been mapped in reconnaissance style (see under Melville Bugt orthogneiss and Lauge Koch Kyst supracrustal complexes). Concentration on coastal areas focussed attention on the Thule Basin that was mapped in its entirety at formational level and followed north onto the adjoining map sheet where the basin margin facies is exposed (Dawes & Garde 2004).…”
Section: Character Of the Survey Mappingmentioning
confidence: 99%
“…Thule mixed-gneiss complex and Prudhoe Land supracrustal complex (see Relationships of the complexes, sections 7, 8) Distribution, composition and metamorphism. The Prudhoe Land granulite complex stretches beyond the map region to north of Sonntag Bugt where it is lost beneath the Inland Ice (Dawes & Garde 2004). The term 'granulite' is used in a metamorphic and lithological sense.…”
Section: Marble (Not In Map Legend)mentioning
confidence: 99%
See 1 more Smart Citation